1994
DOI: 10.1159/000204193
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Symptoms of Hyperhistaminemia after the Treatment of Acute Promyelocytic Leukemia with <i>All-Tran</i><i>s</i> Retinoic Acid

Abstract: A 61-year-old man with acute promyelocytic leukemia (APL) is described in whom some leukemic promyelocytes contained granules similar to those of basophils, and hyperhistaminemia developed after treatment with all-trans retinoic acid. The symptoms of hyperhistaminemia, mediated via H2 receptors, were prevented by the administration of an H2-blocker, famotidine, but wheezing due to bronchospasms, mediated via H1 receptors, developed and was improved by administration of chlorphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In basophilic APL, the leukemic promyelocytes probably differentiate into basophils, causing unusual differentiation syndrome symptoms due to the release of histamine, heparin and cytokines involved in anaphylaxis by basophils. We did not observe a basophils increase during the course of treatment, but our patient experienced various episodes of skin rash and itching, which were successfully treated with endovenous antihistamine therapy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In basophilic APL, the leukemic promyelocytes probably differentiate into basophils, causing unusual differentiation syndrome symptoms due to the release of histamine, heparin and cytokines involved in anaphylaxis by basophils. We did not observe a basophils increase during the course of treatment, but our patient experienced various episodes of skin rash and itching, which were successfully treated with endovenous antihistamine therapy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In promyelocytic leukemia, detection of metachromatic basophilic granulation in the cytoplasm of leukemic promyelocytes, together with the development of hyperhistaminemia, after starting therapy [15,[38][39][40], have long suggested that basophil-associated vasoactive mediators (e.g., heparin, histamine) might be released by those leukemic promyelocytes upon spontaneous or chemotherapyinduced cell differentiation and/or death; thereby, such release of basophil-related contents by these leukemic cells might contribute, at least in part, to the development of an anticoagulant state and a higher risk for severe bleeding. In line with this hypothesis, maturation of leukemic promyelocytes toward the basophil lineage has been recurrently reported in the literature, particularly after all-trans retinoic acid therapy [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%